The Improvement of Discipline and Professional Fiqh Teachers by Supervisors in Islamic Junior High School - Zainuddin Zainuddin; Azizah Azizah; Muhammad Nur (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2022)
The aim of this research was to determine the effectiveness of the supervision of the madrasa supervisors in improving the discipline and professionalism of Islamic Jurisprudence teachers at State MTsN in East Aceh Regency. The problem of this research is how the implementation of supervision of madrasa supervisors in improving the discipline and professionalism of Islamic Jurisprudence teachers at State MTsN in East Aceh Regency, what are the supporting and inhibiting factors, and what solutions are taken to overcome these obstacles? This research used a qualitative approach, located at five MTsN in East Aceh Regency, by interviewing three madrasa supervisors, five MTsN principals, and eight Islamic Jurisprudence teachers. The results showed that the implementation of supervision of madrasa supervisor in improving the discipline and professionalism of Islamic Jurisprudence teachers at MTsN in East Aceh Regency begins with planning, supervision of learning administration, and the learning process. The results have had a positive impact on improving the discipline and professionalism of Islamic Jurisprudence teachers. The supporting factors are the enthusiasm to serve for the advancement of teachers and Islamic schools; the enthusiasm to see the discipline and professionalism of Islamic Jurisprudence teachers; support from the leadership; and good cooperation from madrasa principals. The inhibiting factors are the large number of the assisted madrasa, the lack of supervisors, the long distance to the school, and even to inland areas. The solution is to propose a new supervisor, arrange for the distribution of the assisted madrasa for each supervisor not too far away, and encourage teachers and madrasa principals to be willing to become supervisors.